ASSESSMENT OF MUNICIPAL INVESTMENTS IN TERMS OF SUSTAINABLE DEVELOPMENT ON THE EXAMPLE OF THE MUNICIPALITIES OF OLSZTYN COUNTY - Kozłowski, Waldemar (Management and Administration Journal, 2025)
The complexity of the municipal economy results from various economic, social and ecological features, where social interest is integrated with economic efficiency. Municipal investments are currently one of the key tools of the commune's development strategy. When planning and implementing them, communes pay special attention to their impact or influence on sustainable development in areas such as economy, society, and ecology. The aim of the article is to analyze and assess the role of municipal investments in the aspect of sustainable development of the commune. The subject of the research are municipal investments implemented in the communes of the Olsztyn district. The research was conducted in 2020-2024. The basic research methods used in the study are: critical analysis method and indicator analysis. For the purposes of the research, a model for assessing municipal investments was developed. The research showed that individual communes obtained different levels of sustainable development indicators characteristic of the municipal economy. The research results can be used to analyze and assess the investment strategies of communes, promote best practices, and improve the process of assessing municipal invest-ments from the perspective of sustainable development.